The Protection of Economic Rights of Copyright Holders of Musical Works (Study of Decision Number: 464 K/Pdt.Sus-HKI/2024) - Dewi Sulistianingsih; Renard Kananda Dipta; Andry Setiawan; Yuli Prasetyo Adhi; Hafiz Rafi Uddin (Faculty of Law, Universitas Negeri Semarang, 2026)
This study is intended to examine the application of protection of the economic rights of copyright holders of musical works of art as regulated in Law Number 28 of 2014 concerning Copyright, with a focus on the study of Supreme Court Decision Number 464 K/Pdt.Sus-HKI/2024. This study uses a normative legal approach by collecting data through literature reviews, laws and regulations, official documents, and other legal sources. The problems studied include the form of protection of economic rights in the copyright of musical works and how the legal considerations of the panel of judges in upholding the principle of this protection. The results of the analysis show that economic rights give creators exclusive rights to utilize, reproduce, distribute, and obtain economic benefits from their works. In this case, the Panel of Judges of the Supreme Court concluded that Rahman Efendi as the creator of the song “Nasib Force One Buruk” had his economic rights harmed by Romli through the song “Obuk Celleng” which without permission composed the lyrics, notation, chords, and arrangements. The Panel of Judges overturned the first instance court’s decision, granted Rahman Efendi’s appeal, ordered the revocation of the registration of the song “Obuk Celleng”, and determined the payment of material and immaterial compensation. However, there is potential for legal friction in the judge’s considerations that do not delve into the substance of the violation and focus more on the letter of registration of the creation.